SOSIALISASI PENTINGNYA KESEHATAN MENTAL IBU HAMIL DENGAN SLOGAN “SUAMI” DIJAGA IBU HAMIL SEJAHTERA - Ai Nur Zannah; Laila Karimatu Zalika; Arien Daning Astiti; Eka Afdi Septiyono (LPPM Universitas dr. Soebandi, 2024)
Mental health is an important component of overall well-being, especially for pregnant women. WHO reports that 1 in 5 women will experience a mental health disorder during pregnancy or in the year following childbirth. The impact of mental health disorders on mothers will have a physical and psychological impact on both the mother and her baby such as postpartum depression, and low birth weight babies. The purpose of this community service is to socialize the importance of mental health of pregnant women with the slogan “SUAMI” Guarded by Prosperous Pregnant Women. This community service was conducted with a descriptive approach using the “SUAMI” Slogan (Support system; Unplug from negativity; Positive activities; Me-time; Include adequate rest). The community service targets were 27 third trimester pregnant women who filled out mental health questionnaires before and after the socialization took place. The results of community service show that there is an increase in mental health before and after being given socialization by 28%. Based on the above, it can be concluded that the provision of socialization with the slogan “SUAMI” Guarded by Prosperous Pregnant Women can improve maternal mental health by reducing maternal health problems from anxiety to depression.